The last séance : tales of the supernatural - Christie, Agatha, 1890-1976 (HarperCollinsPublishers, 2019)
Kompendium hororově laděných a jinak mrazivých povídek známé anglické autorky detektivek.
Keywords: anglické povídky; horory (povídky); výbory; English short stories; horror tales; selected works